Enhancing Academic Achievement and Psychological Well-Being Through Self-Efficacy, Self-Regulation, And Social Support: An Organizational Development Intervention Study Among Vocational Game Design Students in Beijing - Zhou, Qing; Kim, Seongdok (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
This study examines the impact of Organizational Development Interventions (ODIs) on self-efficacy, self-regulation, social support, psychological well-being, and academic achievement among 60 second-year vocational Game Design students at Beijing Polytechnic. A mixed-methods approach implemented four interventions— goal-setting workshops, coaching sessions, team-based learning, and positive psychology activities—over one semester. Paired-sample t-tests revealed significant improvements in all variables (p < .001). Qualitative data from interviews, observations, and assignment analyses highlighted increased confidence, structured learning behaviors, peer collaboration, emotional resilience, and academic performance. Rooted in social cognitive theory, self-regulated learning, social support theory, and positive psychology, the findings demonstrate ODIs’ effectiveness in fostering cognitive, behavioral, and emotional growth in creative vocational education. Recommendations inform curriculum development, faculty training, and institutional policy.